2017
DOI: 10.3329/ralf.v4i1.32400
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of selected mass media in agricultural technology transfer to the farmers of Bangladesh

Abstract: Effectiveness Mass media Technology transfer Farmers BangladeshThe role of mass media in dissemination of farm information to the farmers is crucial. Thus, the study was undertaken to determine the effectiveness of selected mass media in agricultural technology transfer to farmers of Bangladesh and identify the influential factors affecting the effectiveness of mass media in technology transfer to farmers. The study was conducted in three villages of Gouripur sub-district under Mymensingh district in Banglades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…Farmers between the ages of 41 and 50 are more likely to patronize agricultural radio programmes than those in the other age groups. The results of this study disagree with that of Khan et al (2017) who reported that there is no positive relationship between the age of the respondent and the patronage of farm radio programmes (Table 9).…”
Section: Association Between Patronage and Agecontrasting
confidence: 99%
See 1 more Smart Citation
“…Farmers between the ages of 41 and 50 are more likely to patronize agricultural radio programmes than those in the other age groups. The results of this study disagree with that of Khan et al (2017) who reported that there is no positive relationship between the age of the respondent and the patronage of farm radio programmes (Table 9).…”
Section: Association Between Patronage and Agecontrasting
confidence: 99%
“…Farmers with a JHS educational level are more likely to patronize agricultural radio programmes than those with no education, those who had primary education and those who had senior high school education. The results of this study agree with that of Ango et al (2013) and Khan et al (2017) who reported that there is positive relationship between formal education and patronage of agricultural radio programmes for agricultural innovation. In general, it is expected that people with high levels of education are expected to learn more from mass media than those with low levels of education (Tichenor et al, 1970).…”
Section: Association Between Patronage and Educational Levelsupporting
confidence: 91%
“…It can therefore be said that the use of mass media in agricultural information dissemination has not produced the expected result. This assertion is made from the definition of effectiveness by Khan, Rahman and Uddin (2017) as the influence or capacity or validity of something to produce expected result.…”
Section: Perceived Effectiveness Of Adp's Use Of Mass Media In Agricultural Information Disseminationmentioning
confidence: 99%
“…Effectiveness of mass media facilitates the adoption of innovation especially when actively put in use and by that encourages agricultural development. Khan, Rahman and Uddin (2017) defines effectiveness as the influence or capacity or validity of something to produce the expected results. Effectiveness in mass media can therefore be referred to as the capacity of mass media to produce expected result.…”
Section: Introductionmentioning
confidence: 99%